Avian pathogenic Escherichia coli-induced activation of chicken macrophage HD11 cells. (October 2018) - Peng, Lianci; Matthijs, Mieke G.R.; Haagsman, Henk P.; Veldhuizen, Edwin J.A.
Abstract: Avian pathogenic Escherichia coli (APEC) can cause severe respiratory diseases in poultry. The initial interaction between APEC and chicken macrophages has not been characterized well and it is unclear how effective chicken macrophages are in neutralizing APEC. Therefore, the effect of APEC on activation of chicken macrophage HD11 cells was studied. Firstly, the effect of temperature (37 vs 41 °C) on phagocytosis of APEC by HD11 cells was determined. The results showed that APEC was more susceptible to being phagocytosed by HD11 cells at 41 °C than 37 °C. Subsequently, the capacity of HD11 cells to kill APEC was shown. In addition, HD11 cells produced nitric oxide (NO) at 18 h post-infection and a strong increase in the mRNA expression of IL-8, IL-6, IL-1β and IL-10 was detected, while IFN-β gene expression remained unaffected. Finally, it was shown that the response of HD11 was partially dependent on viability of APEC since stimulation of HD11 cells with heat-killed APEC resulted in a reduced expression level of these cytokines. In conclusion, APEC induces an effector response in chicken macrophages by enhanced NO production and cytokines gene expression. Highlights: APEC was more efficiently phagocytized by HD11 cells at 41 °C than 37 °C. HD11 cells are capable of killing APEC. Phagocytosis of APEC induces NO production and cytokines expression in HD11 cells.